ANALISIS PENGARUH KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDART (IFRS) TERHADAP EARNINGS MANAGEMENT - Lisa Melyana; Abdul Rohman (Diponegoro Journal of Accounting, 2015)
The research aimed to give empirical evidence concerning the effect of the IFRS adoption on earnings management and the test of the difference of earnings management level between beforeand after the adoption. The adoption of IFRS is a global language in the financial statements that will  improve  the  quality  of  financial  reporting.  Its  indicated  to  reduce  the  level  of  earningsmanagements. The research objects were the manufacturing companies listed in Indonesia Stock Exchange for 4 years (2010-2013). The main variables in this research are IFRS and earnings management (DACC). The research also includes several control variables i.e. size, ROA and operating cash flow (OCF). The data were analyzed by using multiple regression analysis and Wilcoxon Rank Signed different test analysis. In this research, the adoption of IFRS indicates the positive effect on earnings management. The result of different test analysis also indicates that there is a statistically significant difference of earnings management level between before and after the adoption of IFRS. The other result indicates that among the three control variables, ROA and OCF indicate the positive effect on earnings management. Whereas size is found not to have significant effect. Based on this research concluded that the adoption of IFRS has not fully guaranteed a decrease in earnings management yet.